Evaluation of Calu-3 cell lines as an in vitro model to study the inhalation toxicity of flavoring extracts. (24th March 2022) - Ji, Xiaoli; Sheng, Yunhua; Guan, Ying; Li, Yinxia; Xu, Yuqiong; Tang, Liming
Abstract: This study aimed to evaluate the characteristics of Calu-3 cells as a model to examine the toxicological responses of inhalable substances. Calu-3 cells were grown to the confluence at an air-liquid interface (ALI) using a Transwell ® permeable support system. The ALI resulted in biomimetic native bronchial epithelium displaying pseudostratified columnar epithelium with more microvilli and secretory vesicles. We further characterized and optimized the Calu-3 cell line model using ALI culturing conditions, immunolabeling of protein expression, ultrastructural analysis using scanning electron microscopy (SEM), and transepithelial electrical resistance (TEER) measurements, and then screened for the cytotoxicity of tobacco flavoring extracts. Calu-3 cells displayed dose-dependent responses when treated with the flavoring extract. Within 8–10 days, cell monolayers developed TEER ≥1000 Ω·cm 2 . During this time, Calu-3 cells exposed to flavoring extracts X01 and X06 exhibited a loss of cellular integrity and decreased ZO-1 and E-cadherin protein expression. In conclusion, we investigated the Calu-3 cell line culture conditions, culture time, and barrier integrity and tested the effect of six new synthetic tobacco flavoring extracts. Our data demonstrate that the Calu-3 human bronchial epithelial cell monolayer system is a potential in vitro model to assess the inhalation toxicity of inhalable substances.